2009
DOI: 10.1182/blood.v114.22.636.636
|View full text |Cite
|
Sign up to set email alerts
|

AC220, a Potent, Selective, Second Generation FLT3 Receptor Tyrosine Kinase (RTK) Inhibitor, in a First-in-Human (FIH) Phase 1 AML Study.

Abstract: 636 Activating mutations in the FLT3 RTK are present in ∼30% of AML patients (pts), who have a significantly worse prognosis than pts with wild type (WT) FLT3. AC220 is a novel 2nd generation RTK inhibitor with potent in vitro and in vivo activity in FLT3- and KIT-dependent tumor cell lines. It is highly selective for both WT and mutant FLT3 with significant activity against KIT. A first-in-human Phase 1 study investigating AC220 in predominantly relapsed or refractory AML pts, unselected for FL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…[15][16][17][18][19] Several FLT3 inhibitors have been developed in an attempt to overcome this aggressive outcome of FLT3-ITD AML. 20 Clinical responses have been observed with agents such as sorafenib, 21 quizartinib, 22 midostaurin, 23 and others. Responses are frequently characterized by a rapid reduction in peripheral blood and/or bone marrow blasts, but they are usually transient with most patients eventually progressing.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Several FLT3 inhibitors have been developed in an attempt to overcome this aggressive outcome of FLT3-ITD AML. 20 Clinical responses have been observed with agents such as sorafenib, 21 quizartinib, 22 midostaurin, 23 and others. Responses are frequently characterized by a rapid reduction in peripheral blood and/or bone marrow blasts, but they are usually transient with most patients eventually progressing.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven of 45 evaluated patients (24%) experienced transient clinical responses, and four patients achieved a CR with single-agent AC220. Three of the responders harbored FLT3 mutations, but the other responders had WT FLT3 [9]. A phase II trial of AC220 in relapsed/refractory patients with mutant FLT3 AML is currently enrolling patients at multiple institutions (ClinicalTrials.gov identified, NCT00651261).…”
Section: Kw-2449mentioning
confidence: 99%
“…In recent years, attempts have been made to develop more specific and potent inhibitors of FLT3 for clinical investigation. One such agent, AC220, has shown great promise and dramatic responses in early-phase trials of patients with AML [9].…”
Section: Introductionmentioning
confidence: 99%
“…AC220 has been explored in a phase 1 dose-finding and safety trial in 76 elderly patients with either relapsed or refractory AML or untreated AML. 99 The MTD was identified as AC220 200 mg once daily on a continuous dosing schedule. Pharmacokinetic evaluation of treated patients revealed that AC220 potently inhibited phosphorylated FLT3 in FLT3-ITD cells at this dose.…”
Section: Sunitinibmentioning
confidence: 99%
“…The most commonly reported AEs that may have been drug-related were mainly grade 2 and included peripheral edema, dysgeusia, and nausea. 99…”
Section: Sunitinibmentioning
confidence: 99%